Gendered spaces - Spain, Daphne (Chapel Hill : University of North Carolina Press, 1992)
The history of spatial segregation at home and in the workplace and how it reinforces women's inequality.
Space and status -- The Mongolian ger and the Tuareg tent -- Ceremonial men's huts -- The spatial division of labor -- From parlor to great room -- Education -- The nineteenth-century workplace -- The contemporary workplace -- Degendering spaces.
Includes bibliographical references (pages 269-289) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Sex discrimination against women -- History; Space (Architecture) -- History; Sex role -- History; Social status -- History; Women -- Dwellings -- History; Sexual division of labor -- History; Sex role in the work environment -- History; Women -- Habitations -- History; Discrimination à l'égard des femmes -- Histoire; Espace (Architecture) -- Histoire; Rôle selon le sexe -- Histoire; Statut social -- Histoire; Femmes -- Habitations -- Histoire; Rôle selon le sexe en milieu de travail -- Histoire; Division sexuelle du travail -- Histoire; SOCIAL SCIENCE -- Gender Studies; Sex discrimination against women; Sex role; Sex role in the work environment; Sexual division of labor; Social status; Space (Architecture); Women -- Dwellings; Raumaufteilung; Geschlechtertrennung; Frau; Mann; Sekseverschillen; Sociale ongelijkheid; Ruimtelijke aspecten; Sexisme -- Histoire; Espace (architecture) -- Histoire; Rôle selon le sexe -- Histoire; Discrimination sexuelle dans l'emploi -- Histoire; Division sexuelle du travail -- Histoire; Statut social -- Histoire; Femmes -- Habitations -- Histoire; History